2010
DOI: 10.1117/12.860631
|View full text |Cite
|
Sign up to set email alerts
|

Advances in oligothiophene-based conductors and semiconductors for printed electronics

Abstract: PEDOT based polyelectrolyte complexes are widely used as hole injection layers in OLEDs. They are available with high and low work functions. A new polystyrenesulfonic acid free water based complex has been developed that offers easy processing. Due to its high stability it gives rise to efficient and long living devices.Small molecule semiconductors can exhibit high charge carrier mobilities due to their high crystallinity. Oligomeric semiconductor materials with mobilities >3 cm 2 /Vs have been synthesized u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Oligothiophenes (oT), polythiophene (nT), and their derivatives are conjugated molecular systems that exhibit narrow and tunable optical band gaps and high conductivity. Because of these outstanding molecular properties, they have been widely used as functional materials in organic electronic devices such as field-effect transistors, organic light-emitting diodes, , organic photovoltaic devices (OPVs), , and bioelectronics. , As a derivative of nT, poly­(3-hexylthiophene-2,5-diyl) (P3HT) is a widely used donor material blended with phenyl-C 61 -butyric acid methyl ester in bulk heterojunction (BHJ) OPVs. , As a small molecule alternative to polymer-based BHJs, sexithiophene (6T)-based BHJs are considered to be more structurally tunable. Due to shallow (i.e., not far in energy below the vacuum level) highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) levels, oTs and nTs are most commonly used as electron donors in organic electronic devices. Previous studies have shown that multiple oxidation states are accessible for the oligothiophenes and their derivatives via electrochemical , and chemical oxidation; however, there have been no instances of oT reduction chemistry reported to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oligothiophenes (oT), polythiophene (nT), and their derivatives are conjugated molecular systems that exhibit narrow and tunable optical band gaps and high conductivity. Because of these outstanding molecular properties, they have been widely used as functional materials in organic electronic devices such as field-effect transistors, organic light-emitting diodes, , organic photovoltaic devices (OPVs), , and bioelectronics. , As a derivative of nT, poly­(3-hexylthiophene-2,5-diyl) (P3HT) is a widely used donor material blended with phenyl-C 61 -butyric acid methyl ester in bulk heterojunction (BHJ) OPVs. , As a small molecule alternative to polymer-based BHJs, sexithiophene (6T)-based BHJs are considered to be more structurally tunable. Due to shallow (i.e., not far in energy below the vacuum level) highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) levels, oTs and nTs are most commonly used as electron donors in organic electronic devices. Previous studies have shown that multiple oxidation states are accessible for the oligothiophenes and their derivatives via electrochemical , and chemical oxidation; however, there have been no instances of oT reduction chemistry reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Oligothiophenes (oT), polythiophene (nT), and their derivatives are conjugated molecular systems that exhibit narrow and tunable optical band gaps and high conductivity. 1−4 Because of these outstanding molecular properties, they have been widely used as functional materials in organic electronic devices such as field-effect transistors, 5−10 organic light-emitting diodes, 11,12 organic photovoltaic devices (OPVs), 13,14 and bioelectronics. 15,16 As a derivative of nT, poly(3-hexylthiophene-2,5-diyl) (P3HT) is a widely used donor material blended with phenyl-C 61 -butyric acid methyl ester in bulk heterojunction (BHJ) OPVs.…”
Section: ■ Introductionmentioning
confidence: 99%